Validation of Loan Applicants Using Environmental, Social, and Governance Indicators - Aghaei, Vahid; Seiedkhani, Reza; Mohammadipour, Rahmatollah; Feizollahi, Sadegh; Moradpour , Mojtaba (Management Strategies and Engineering Sciences, 2024)
This study examines the impact of Environmental, Social, and Governance (ESG) indicators on the selection and ranking performance of corporate banking clients. Given the increasing importance of sustainability in financial systems, this research seeks to investigate the effects of ESG indicators on reducing credit risk and improving financial performance. The data utilized includes information from clients of selected banks in emerging markets and has been analyzed using advanced econometric methods. The results indicate that ESG indicators play a significant role in reducing financing costs and enhancing investor confidence. Furthermore, banks that are leaders in implementing ESG criteria have achieved more sustainable performance through better risk management. Finally, it is suggested that standardized policy and reporting frameworks be designed in developing countries to facilitate the implementation of ESG criteria.